DISTILLERY SPENTWASH IN THE CONTEXT OF CROP PRODUCTION – A REVIEW - S. K. RAJKISHORE; N. S. VIGNESH (The Bioscan, 2012)
Post-methanated distillery spentwash (PMDSW) is a by-product of sugar industry often used as a source of nutrients for a wide array of crops. In the past four decades, PMDSW has been extensively studied in various crop production systems that brought out benefits and concerns associated with this industrial waste water. This review encompasses the impact of PMDSW on changes in soil physical, chemical and biological characteristics, shift in ground water quality, long-term effects and responses of crops. This paper has clearly suggested that the spentwash application has resulted in the changes of soil properties such as impeded hydraulic conductivity, build up of salinity and restricted biological activity transiently as a secondary consequence of intense salt stress. Despite these ill-effects, PMDSW carries macro and micronutrients that facilitate better growth and yield performance in almost all crops that have been experimented. One of the potential hazards associated with PMDSW is the interference with groundwater which is rarely reported or critically analyzed in the context of seasonal and temporal shifts. Overall, this review suggests that the PMDSW can be exploited as a source of nutrients to sustain the crop production with a rider that excessive or continuous use need to be circumvented.